An Empirical Study On The International Transmission Of Price Events Through The Interaction of Prices In Capital Flows- A Study Of The Indian And The US Economies - Gupta, Shruti (2007)
The last few years have seen a boom in financial markets in the developing world especially in terms of the amount of cross- border transfer of capital that has been occurring between developed and developing economies. Capital flows today have become an essential ingredient for the growth and development of a country. But on the flip side, excess of it can cause so much volatility that the economy can crash as was seen in the Asian and Mexican crises. The characteristic features of such phenomenal volumes of cross border transfer of capital are the increased amount of inter-dependence between stock exchanges across the globe and the transmission of potential problems from one country to another. The effect this inter-dependence has on stock price movements between stock exchanges resulting in capital to flow into or out of a country is the aim of this research. With the opening up of the Indian economy in 1991, there has been a stupendous inflow of capital into the financial markets. The country has grown heaps and bounds ever since its capital reserves reached US$ 1 billion in 1991.Today her reserves are sufficient enough to protect her financial markets from any adversities if the need arises. But the question that needs to be addressed here is: what is the effect of financially influential developed economies like America on smaller less developed economies like India? Is too much inter-dependence between the two countries posing a potential problem for India? These questions are answered by conducting a quantitative research to investigate the movements between the New York Stock Exchange for America and the National Stock Exchange for India. The research uses theory coupled with computer simulations and regressions to look into the effect of price movements between the two stock exchanges. It also tries to analyze the outcome of such movements which could possibly lead to a crash in the Indian economy. It also looks into the aspect of future predictions for the two economies.